Analisis Pola Perdagangan dan Daya Saing Minyak Kelapa Sawit (CPO) Indonesia - Ahmad Rifai; Dini Septianingsih Ginting; Yeni Kusumawaty (Universitas Medan Area, 2023)
Indonesia is an agrarian country whose economy is supported by the agricultural sector with plantations as the dominant sub-sector and makes the CPO has an imporkan role in Indonesia's export structure. The accumulated export value of Indonesian palm oil during 2001-2021 was USD 253.42 million, far greater than the accumulated value of imports of USD 208,133. Indonesian CPO is the largest foreign exchange earner from the export value of the processing industry, but on the other hand Indonesia also has considerable trade interactions with India and China in particular. So an analysis of trade patterns and the competitiveness of Indonesian palm oil commodities with trading partners is important to understand Indonesia's competitiveness in the trade of palm oil commodities and their derivatives against 10 of Indonesia's main trading partner countries for 21 years, namely 2001-2021. Analysis IIT is used as an indicator to analyze trade patterns of commodity palm oil HS code 1511 and its derivatives HS code 151190. RSCA and TII is used as a measure of the competitiveness of Indonesia's palm oil exports. The results showed that the pattern of trade in Indonesian palm oil was not integrated in 9 trading partner countries, meaning that there was no two-way trade between Indonesia and trading partner countries because Indonesia only exports and does not import palm oil and its derivatives. Indonesia is proven to have a comparative advantage in world palm oil exports with the intensity index of Indonesia's bilateral trade with 9 countries being greater than expected.